Investigating the Impact of Digital Leadership Dimensions on Service Economics Dimensions: An Empirical Study of Service Ministries in the Kingdom of Saudi Arabia - Abdulrahman, Badreldin Mohamed Ahmed; Mohammed, Sanaa Mostafa (International Review of Management and Marketing, 2024)
This study examines the influence of various aspects of digital leadership (such as digital culture, visionary planning, system design, empowering leadership, employee development, innovation, persuasion, and knowledge) on different dimensions of service economics (including innovative economic ideas, efficient use of economic resources, leadership behaviors, and economic learning) within service ministries in the Kingdom of Saudi Arabia. We used a quantitative technique to collect data from a sample of 475 workers involved in service ministries via the use of a survey questionnaire. We conducted a thorough study of the data using the method of multiple regression analysis. The findings indicate that the different components of digital leadership have a significant and advantageous impact on the variables associated with service economics. The research determined that digital culture, innovation, and employee professional development are the main characteristics that have a major impact on digital leadership. This study contributes to the current literature by providing empirical evidence on the relationship between digital leadership and service economics. Additionally, it offers practical suggestions for service ministries in Saudi Arabia to enhance their service economics via the implementation of effective digital leadership methods. Nevertheless, the study is subject to many limitations, including its cross-sectional design and its narrow emphasis on a particular environment. It is recommended that future research endeavors address these constraints.